Bletilla striata Oligosaccharides Improve Ulcerative Colitis by Regulating Gut Microbiota and Intestinal Metabolites in Dextran Sulfate Sodium-Induced Mice - Zhu, Tianxiang; Hu, Baifei; Ye, Cheng; Hu, Haiming; Yin, Mingzhu; Zhang, Zhigang; Li, Shuiqing; Liu, Yanju; Liu, Hongtao (Frontiers in Pharmacology, 2022)
This study aimed to elucidate the mechanism of Bletilla striata oligosaccharides (BO) in the treatment of ulcerative colitis (UC). A UC mouse model was induced by 3% Dextran sodium sulfate (DSS), and BO (1 mg/mL in water) were administered for intervention. The results show that BO effectively inhibited the release of intestinal inflammatory cytokines such as Il-6, Tnf-α, and Il-1β. Also, BO profoundly elevated the secretion of mucins and the expression of tight junction (TJ) proteins to attenuate dysfunction of the intestinal barrier. The 16S rDNA sequencing and liquid chromatography/gas chromatography-mass spectrometer (LC/GC-MS) analysis of mouse feces revealed that BO regulated the disturbance of gut microbiota and intestinal metabolites. By using the in vitro fermentation broth of BO and gut microbiota-depleted mice treated with antibiotics, we confirmed the protection of BO against UC. In conclusion, BO played a role in improving UC by modulating gut microbial composition and intestinal metabolites, which provided new therapeutic strategies for UC treatment.